Rancang Bangun Sistem Pakar dengan Metode Forward Chaining untuk Rekomendasi Pariwisata di Labuan Bajo Menggunakan iOS Platform - Leonardo Jeffry Sutedjo; Rinabi Tanamal (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Nowadays many tourists like to travel. When on vacation the user is confused about where to go and whether it's good or not. When tourists want to take a vacation and the user must choose to do a tour and it turns out that it is not good in terms of good or bad attractions. So there is encouragement to help tourists to provide recommendations for good tourist places to visit. But now with so many online media to buy tickets, but the local guide is still rampant in maintaining tourism. This location with the presence of local guides who do not understand the price and when they are in Labuan Bajo the price of the user is still not right then it makes tourists confused. The existence of a problem raises the urge to make an application of an expert system that recommends tourist attractions in Labuan Bajo by using the Forward Chaining method. In making this application uses a rule based to process data on applications on iOS. And using mcgoo is used to create and process data taken from experts. This application can help tourists to find excellent places to travel. Because the purpose of the user to travel is to have fun if the user is confused to determine the existing location then this application will help the user determine the desired tourist attractions. This application also provides several tourist options such as tours on the sea, cities, or hills/mountains. The target of visitors is always less because tourists lack the desire to travel in Labuan Bajo because of the lack of recommendations on Labuan Bajo tourism. The results of research conducted by more foreign tourists who prefer to visit Labuan Bajo because local tourists prefer tourist destinations that are still crowded, such as Bali and Lombok. So that makes tourism in Labuan Bajo not yet an attraction for local tourists.